Biomass Equations for Tropical Tree Plantation Species in Young Stands Using Secondary Data from the Philippines - Banaticla, Ma. Regina N.; Sales, Renezita F.; Lasco, Rodel D. (Annals of Tropical Research, 2007)
Estimation of the magnitude of sinks and sources of carbon requires reliable estimates of the biomass of forests and of individual trees. Equations for predicting tree biomass have been developed using secondary data involving destructive sampling in plantations (mostly less than 10 years of age) in several localities in the Philippines. These equations allow estimates of carbon sequestration to be made at much lower cost than would be incurred if detailed stand inventories were undertaken. The species in the study reposted here include Gmelina arborea Roxb., Parasenrianthes falcataria (L.) Nielsen Swietenia macrophylla King and Dipterocarp species in Mindanao, and Leucaena leucocephala de Wit from Laguna, Antique, Cebu, Iloilo, Rizal, and Ilocos Sur. Non-linear regression was used to derive species-specific, site-species and generic equations between yield and diameter of the form y = αDβ. Equations were evaluated based on the correlation coefficient, standard error of estimate and residual plots. Regressions resulted in high r values (>0.90). In some cases, non-homogeneous variance was encountered. The generic equation improved estimates compared with models used in previous studies.